(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2021)
Despite the advent of over-the-top platforms, linear television still remains the dominant medium in European markets. This article provides a case study of the circulation of non-French European crime series in the French televisual landscape. It is based on a diachronic analysis of the flow of TV crime shows produced in Europe and broadcasted in France from 1957 to 2018. The data was collected from the official French TV archives as well as from experts and professional sources such as TV programme guides, databases, newspaper articles or amateur sources. All national channels were taken into account, be they state television, mainstream commercial channels or cable channels, except for OTT platforms. The analysis, based on format studies, provides three main results. First, the circulation of European TV crime series in France is rooted in an industrial process. It entails a process of indigenization performed through human mediation in order to fit into the culture and industry of the broadcasting territory. The second result tempers the ideal of European cultural diversity. Indeed, a diachronic perspective highlights the limited cultural diversity in this field, as German, British and Nordic Noir productions dominate European TV crime series. Lastly, data indicate continued issues with gender and ethnic equality in media industries, as crime narratives are still construed by a white and male-dominated creative industry.